Bizkaiera zaharra euskalkien artean - Lakarra, Joseba Andoni (Anuario del Seminario de Filología Vasca "Julio de Urquijo", 1986)
Among the Basque dialects, Biscayan occupies a marginal position which has led some researchers to view it as an exception or even as lying in opposition to the rest. Lacombe (1924) thus proposes a bipartite division of the Basque dialects (Biscayan versus the rest), and Uhlenbeck (1947) goes even futher, maintaining that the language of origin of the Biscayan dialect is different from that of the Guipuzcoan, Labourdin and the others, and that only an uninterrupted process of mutual approximation has suceeded in partially erasing the differences, which were previously clearer. Following Tovar (1959) and above all Mitxelena (1964 and 1977), we demonstrate that, on the contrary, the Biscayan does not stem from a separate tongue from that which gave rise to the other Basque dialects but in fact derives from the same language. The evidence of the texts written in old Biscayan (15th century to 1745) is repeatedly turned to, and plainly permits us to reject Uhlenbeck’s claim, since the B. dialect was actually much closer to the other Basque dialects four centuries ago than it is now. A close analysis of these texts reveals a progressive distancing of the dialects in question; however, this is not peculiar to that of Biscay, but it is a general occurrence among all of them and, by and large, among all linguistic forms that derive from a single pre-existing unit. Abundant examples are given of dialectal differences that are due to the preservation of archaic forms, divergent preferences and local innovations, the examples coming from basically morphological data. There follows an attempt at a statistical analysis of the same data, which indicates that the modern B. and G. have far fewer features in common than do the old dialects of the same two provinces, in spite of sharing many innovations. We point out that little is to be gained from comparisons based on the literary forms of the dialects, since the picture these give us is likely to be simplistic and deformed; this is particularly the case of "hiperbiscayan" (cf Laka 1986) and other forms which are based on the notion of uniting the dialects. Examples are given of items which extend totally across various dialects, and, alternatively, of others which extend across one or more dialectal areas without totally covering any. It is shown how differentiated sub-dialects also existed in the old B. Finally (following BILE et al, 1984), we call for a more precise knowledge of both old and modern dialectal varIeties, and suggest the need for monographic studies free from the prejudiced of comparison; only at this price can be the basis of future comparisons and historical analyses be assured.